1995
DOI: 10.1152/ajpheart.1995.269.4.h1379
|View full text |Cite
|
Sign up to set email alerts
|

Role of NO mechanism in cardiovascular effects of diaspirin cross-linked hemoglobin in anesthetized rats

Abstract: The role of nitric oxide (NO) in the cardiovascular actions of diaspirin cross-linked hemoglobin (DCLHb) was studied in anesthetized rats. The regional circulatory and systemic hemodynamic effects of DCLHb (400 mg/kg iv) were studied using a radioactive microsphere technique in control (untreated) and L-arginine (a NO precursor) pretreated rats. DCLHb produced a significant increase in blood pressure (75%), cardiac output (42%), stroke volume (36%), and total peripheral resistance (45%), without affecting hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 0 publications
5
50
0
1
Order By: Relevance
“…Sharma and colleagues (16) reported that co-infusion of L-arginine diminishes the hemodynamic responses to diaspirin cross-linked hemoglobin, a monomeric hemoglobin. Similar results with L-arginine were reported by Katsuyama et al (43) who also showed that inhibition of NO synthesis by N -nitro-L-arginine attenuates the hypertensive response to diaspirin cross-linked hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma and colleagues (16) reported that co-infusion of L-arginine diminishes the hemodynamic responses to diaspirin cross-linked hemoglobin, a monomeric hemoglobin. Similar results with L-arginine were reported by Katsuyama et al (43) who also showed that inhibition of NO synthesis by N -nitro-L-arginine attenuates the hypertensive response to diaspirin cross-linked hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO), an important mediator of vasodilation and other physiological processes (13), is known to react rapidly with the oxyHb (14) forming metHb (Fe 3ϩ ) and NO 3 Ϫ or to bind to deoxyHb, essentially scavenging the NO and causing vasoconstriction. Scavenging of NO by hemoglobin is thought to contribute to the hypertensive response observed with many cell-free hemoglobin solutions in intact animals (15,16), perfused organs (17,18), and isolated vascular preparations (19,20). We have recently shown that genetic modification of the distal heme pocket to reduce the rate of NO scavenging, measured in vitro, can essentially eliminate the hemoglobin-induced pressor response (21).…”
mentioning
confidence: 99%
“…[17][18][19][20] They are also consistent with the observed effect of free Hb products on systemic blood pressure (hypertension). 21,22 In addition to the oxidation and addition reactions of Hb with NO, a third, reversible reaction involving S-nitrosation of the ␤-cys93 residue to form SNO-Hb may be of physiological importance, thus making the relationship between Hb, NO, and vascular tone more complex than previously appreciated. The detection of an arterial-venous gradient in SNOHb 9 and evidence that administered SNO-Hb reduces systemic blood pressure 9,11 and increases cerebral blood flow 11 has led to the hypothesis that Hb is an active regulator of vascular tone.…”
Section: Hb No and The Pulmonary Circulationmentioning
confidence: 99%
“…1,21,22 These effects can be reduced by intra-and intermolecular cross-linking and conjugation of the Hb molecule to prevent abluminal movement. 28,29 The effects of modified HBOCs on the pulmonary circulation have not been rigorously studied, and there are no reports of the effects of these products on HPV to our knowledge.…”
Section: Hb Modification and Hpvmentioning
confidence: 99%
“…The increased ability of cell-free Hb to scavenge NO has been widely attributed to the hypertension, increased systemic and pulmonary vascular resistance, and morbidity and mortality associated with administration of hemoglobin-based oxygen carriers (HBOCs or "blood substitutes") [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. More recently, the importance of intravascular hemolysis on NO bioavailability in diseased states including hemolytic anemias like sickle cell disease and paroxysmal nocturnal hemoglobinuria (PNH), thalassemia intermedia, malaria, thrombotic thrombocytopenic purpura, hemolytic uremic syndrome and cardiopulmonary bypass has been elucidated [17][18][19][68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%